Structural, optical and morphological properties of Ga1?xMnxAs thin films deposited by magnetron sputtering for spintronic device applications (2012)
In this work, GaMnAs alloy materials were deposited on 7059 Corning glass and GaAs (1 0 0) substrates via RF magnetron sputtering technique. A concentration of Mn about 0.28 was obtained by Energy Dispersive X-ray spectroscopy. The substrate temperature was changed from 440 to 520 °C and layer thicknesses between 172 and 514 nm were obtained. Characterization by atomic force microscopy and X-ray diffraction were performed to determinate surface morphology and crystal structure, respectively. From transmittance spectral measurements we were able to determine optical constants: band gap energy (Eg), absorption coefficient (?), and refraction index (n). A correlation between morphological properties and substrate type was also studied. Diluted magnetic semiconductors like GaMnAs are considered among promising materials for the development of new spin-electronic devices.